Sandcastle Worm-Inspired Polyelectrolyte Hydrogel as a Bioadhesive for Diverse Tissues - Jing Cong (519038) (2025)
Bioadhesives have been widely applied in wound healing and hemostasis, as well as biointegrated devices. Most existing bioadhesives still lack fast adhesion formation, strong interfacial toughness, and outstanding compatibility in humidity environments. Here, we synthesized a polyampholyte hydrogel using oppositely charged acrylic acid and 2-(dimethylamino)ethyl methacrylate, inspired by the sandcastle worms. The anions and cations formed ionic bonds and endowed the hydrogel with outstanding mechanical properties, while the acrylic acids provided abundant carboxylic acid groups and created immediate physical cross-links with the wet tissue surface, allowing for fast and strong adhesion to various tissues and organs under physiological conditions. Moreover, the bioinspired hydrogels displayed outstanding in vivo and in vitro biocompatibility and degradability, significantly promoting wound healing and suppressing inflammation as a bioadhesive. The developed bioinspired polyelectrolyte hydrogel provides an avenue for wound care, as well as other potential medical applications.